Reproductive Rights Under Siege: The Global Backslide on Abortion Laws and Its Social Impact - Felix Schmidt; Eva Zimmermann; Sofia Oliveira (Artes Libres Institutum, 2025)
In recent years, several countries have witnessed a significant rollback of reproductive rights, particularly concerning access to safe and legal abortion. This paper analyzes this global regression through a comparative socio-legal study of abortion law reforms in the United States, Poland, and selected Latin American countries. It explores how populist politics, religious conservatism, and patriarchal legal cultures have converged to curtail reproductive autonomy, despite international commitments to gender equality and health rights. The novelty of this paper lies in its cross-regional legal analysis that connects the rollback of abortion rights to broader socio-political trends, including democratic backsliding and shrinking civic space. While much of the literature treats abortion law as a domestic matter, this study situates reproductive rights within international legal debates on bodily autonomy, gender justice, and human rights universality. The research contributes to feminist legal scholarship by arguing that the erosion of abortion access is not only a health crisis but a structural legal injustice with wide-reaching social impacts—particularly for poor, rural, and minority women. It calls for renewed international legal advocacy and solidarity across jurisdictions, emphasizing the need to embed reproductive rights within binding human rights frameworks and regional legal mechanisms. The paper concludes by offering strategic legal and policy pathways for restoring reproductive autonomy, including transnational litigation, rights-based constitutionalism, and feminist legal mobilization.